Cakupan Imunisasi Dasar dengan Kejadian ISPA pada Balita Usia 1-3 Tahun di Wilayah Puskesmas Wonosari 1 Kabupaten Gunungkidul - Ibnu Malik; Ircham Machfoedz; Mahfud Mahfud (Alma Ata University Press, 2015)
ARIs is one of a health problem that exists in the developing countries and developed countries, this is due to high numbers since it is still in pain (morbidity) and the death rate (mortalily). A disease of ARIs in Yogyakarta still into a disease that most numerous in suffered by fives visit in all Puskesmas in the province of DIY. Especially in Puskesmas Wonosari 1 with average of ARIs patient were 576 toddlers every year. The purpose of this study was to identify relationship between basic immunization and Acute Respiratory Infections (ARIs) in toddlers aged 1-3 years in the region of Puskesmas Wonosari 1 Gunungkidul district. This research was inductive with the cross sectional design. The population were 144 of respondents. Samples was obtained by purposive of sampling techniques which consisted of 50 respondents. An instrument used questionnaire, a pen and the interview. Analysis test used Chi-square. The Results of this research Indicated that the proportion toddlers of ARIs was 31 (62%) toddlers and babies with incomplete basic immunization were 17 (17%). A table cross between the basic immunization and ARIs obtained the value of p=0.033. In conclusion, There was a negative relationship between basic immunization and Acute Respiratory Infections (ARIs) in toddlers aged 1-3 years in the region of Puskesmas Wonosari 1 Gunungkidul district.